CALCULATION OF THE MINIMAL LENGTH OF THE HIGH–SPEED LINE - Nachtigall, Petr; Tischer, Erik (České vysoké učení technické v Praze, 2021)
This paper explores the minimum length of continuous sections of the high-speed line. The minimum length is examined in terms of the maximum speed of high-speed vehicles. Both traditional trainsets consisting of traction units and coaches, and train units were selected for examination. The graphs present the difference in the ability of the different vehicles to reach and use the maximum speed.
Výpočet minimální délky úseku vysokorychlostní trati
Keywords: high-speed line; OpenTrack; simulation; track speed